Cellular Senescence: Mechanisms, Morphology, and Mouse Models. Issue 6 (November 2020) - Beck, Jessica; Horikawa, Izumi; Harris, Curtis
Cellular senescence is a cell cycle arrest in damaged or aged cells. Although this represents a critical mechanism of tumor suppression, persistence of senescent cells during aging induces chronic inflammation and tissue dysfunction through the adoption of the senescence-associated secretory phenotype (SASP). This has been shown to promote the progression of age-associated diseases such as Alzheimer's disease, pulmonary fibrosis, and atherosclerosis. As the global population ages, the role of cellular senescence in disease is becoming a more critical area of research. In this review, mechanisms, biomarkers, and pathology of cellular senescence and SASP are described with a brief discussion of literature supporting a role for cellular senescence in veterinary diseases. Cell culture and mouse models used in senescence studies are also reviewed including the senescence-accelerated mouse—prone (SAMP), senescence pathway knockout mice (p53, p21 [CDKN1A], and p16 [CDKN2A]), and the more recently developed senolysis mice, which allow for direct visualization and elimination (or lysis) of senescent cells in live mice (p16-3MR and INK-ATTAC). These and other mouse models have demonstrated the importance of cellular senescence in embryogenesis and wound healing but have also identified a therapeutic benefit for targeting persistent senescent cells in age-associated diseases including neurodegeneration, diabetes, and cardiac fibrosis.